O funeral de Otávio Augusto e a memória do Princeps nas obras de Tácito, Suetônio e Dion Cássio - Arima, Paulo Yoke Oliveira (2018)
A present dissertation investigates or funeral of Augustus, pois, as apontam os records document, as, for example, Tacitus and Dion Cássio, or funeral procession foi um mechanism of representation of social memory. Nele evokes-se or passado to disclose to life two falees. We courted celebram-is familiar relações, to identity of cidadão, to history of death and to comunidade. Assim, interessa-us compreender os funerais imperiais as espetáculos that are articulated to the relações de poder, a time that is commemorated to life of Princeps e sua divinizazação. Dessa form, ao we will use historiografia antiga, we will analyze or Augustus's funeral on the otic of Tacitus, Suetonium and Dion Cássio, who will serve as a source for our research and who constitute memory repositories built in different periods.